Assyromania and more: in memory of Samuel M. Paley - Pedde, Friedhelm; Shelley, Nathanael ca. 20./21. Jh.; Paley, Samuel M. (marru, 2018)
Intro -- Contents -- Tabula Amicorum -- Foreword of the Editors -- Biographical Portrait -- Publications of Samuel M. Paley -- Prisms of Light -- Speculations on the Original Function of Phlamoudhi-Vounari (Allan S. Gilbert and Ian J. Cohn) -- Exploring Regional Development in Late Bronze I Cyprus. Phlamoudhi-Vounari and the Karpass Peninsula (Mara T. Horowitz) -- Looking for Leucolla (Robert R. Stieglitz) -- Children and Bangles in the Late Second-Millennium BCE Southern Levant (Susan L. Braunstein) -- Working with Sam. From New York City to Tel el Ifshar, Ashurnasirpal II's Northwest Palace, Alişar Höyük and Beyond (Alison B. Snyder) -- Sam Paley at Çadır Höyük 1993-2008. Excavating the Second Millennium BCE (Sharon R. Steadman and Gregory McMahon) -- Seyitömer Mound Excavations (A. Nejat Bilgen) -- Economy and Power. Achaemenid Influence on Regional Economies in Western Anatolia (Lisa Kealhofer, Peter Grave, and A. Nejat Bilgen) -- Megaron 3. The 8th - Early 7th Century BC Palace of the Phrygian Kings at Gordion (Oscar White Muscarella) -- Reconsidering the Position of Mt. Puškurunuwa and Other Issues of Central Anatolian Geography(Ronald L. Gorny) -- From Cyprus to Assyria. Earrings in Middle Assyrian Assur-A Connection to the West (Friedhelm Pedde) -- Tell Billa's Bull Pendant. A Connection to Middle Assyrian Assur (Reed Charles Goodman) -- Representing Cities in Syro-Anatolian and Neo-Assyrian Art (James F. Osborne) -- Timing Space / Spacing Time. Narrative Principles in Assurbanipal Hunt Reliefs of Room C in the North Palace of Nineveh (Davide Nadali) -- The Assur Project in Berlin. A Look Back at Twenty Years of Research (Friedhelm Pedde) -- In Pursuit of the "Missing" Central Palace of Tiglathpileser III at Nimrud (Julian Edgeworth Reade and Donald H. Sanders) -- Recreating Ancient Architecture for Museum Exhibitions (Joanna S. Smith).